'Singing for the Brain': A qualitative study exploring the health and well-being benefits of singing for people with dementia and their carers. (November 2016) - Osman, Sara Eldirdiry; Tischler, Victoria; Schneider, Justine
Dementia has detrimental effects on cognitive, psychological and behavioural functioning, as well as significant impact on those who provide care. There is a need to find suitable psychosocial interventions to help manage the condition, enhance well-being, and to provide support for caregivers. This study explored the impact of Singing for the Brain™, an intervention based on group singing activities developed by The Alzheimer's Society for people with dementia and their carers. This qualitative study used semi-structured interviews with people with dementia and their carers. Ten interviews involving 20 participants were analysed thematically. Social inclusiveness and improvements in relationships, memory and mood were found to be especially important to participants. As well as enjoying the sessions, participants found that attending Singing for the Brain™ helped in accepting and coping with dementia.